OsHAK1 controls the vegetative growth and panicle fertility of rice by its effect on potassium-mediated sugar metabolism. (September 2018) - Chen, Guang; Zhang, Yu; Ruan, Banpu; Guo, Longbiao; Zeng, Dali; Gao, Zhenyu; Zhu, Li; Hu, Jiang; Ren, Deyong; Yu, Ling; Xu, Guohua; Qian, Qian
Abstract: Plant growth and reproduction are both energy-requiring processes; the necessary energy is supplied by the products of photosynthesis. Both the vegetative growth and reproductive success of rice are compromised by the absence of a functional copy of the gene OsHAK1 . Here, a comparison between wild type rice and OsHAK1 knockout mutants not only confirmed the known detrimental effect of the absence of OsHAK1 on root growth, pollen viability and fertility, but also showed that sucrose phosphate synthase activity was lowered, and the sucrose content of the leaves was markedly increased, due to a partial block on the up-loading of sucrose into the phloem. The impaired allocation of sugar to the roots and spikelets caused by the knocking out of OsHAK1 was accompanied by a down-regulation in the leaf sheaths and panicle axes of genes encoding sucrose transporters ( SUT genes), which are active in the phloem, as well as in the roots and spikelets of those encoding monosaccharide transporters ( MST genes), which transport hexose sugars across the plant plasma membrane. The activity of sucrose synthase, acid invertase and neutral invertase in the roots of mutant plants assayed at the tillering stage, and in their spikelets, assayed during grain-filling, was significantly lower than in the equivalent organs of wild type plants. As a result, the supply of total soluble sugar, glucose and fructose to sink organs was reduced, consistent with the effect of the mutation on root growth and panicle fertility. Compared to wild type plants, the mutants accumulated less potassium (K) throughout the plant. The conclusion was that the failure to fully supply the demand of the mutant's sink organs for assimilate was responsible for its compromised phenotype, and that the deficiency in K uptake induced by the loss of OsHAK1 functionality was responsible for the disruption of sugar metabolism.